Psychological stress and its relationship to the use of technology and some demographic variables among a sample of employees in the Sudanese capital, Khartoum - Omer, Tahani Hassan (Journal of Educational and Psychological Sciences, 2022)
The study aimed to find the relationship between psychological stress and the usage of technology such as computers and mobile phones. Therefore, the researcher used the descriptive-analytical method. The sample consists of 200 men and women aged between 20-60 years old, from Al Neelain University, Khartoum University, Omdurman Islamic University, and the Humanitarian Aid and Development Organization. The study measures were the psychological stress scale of Fontana and Reda Abu saree, and its identification of demographic factors represented in gender, age, blood type, material status, and work.After applying the measurements to the sample, the researcher performed a statistical analysis of the data using SPSS and found that: 1- In general, there is no correlation between psychological stress and the use of technology among computer and mobile phone users since this association is characterised by being low.2- There is a statistically significant relationship between psychological stress and technology usage; the standard deviation for the computer was (4.3325) compared to (2.4694) for the mobile phone.3- There are statistically significant differences in psychological stress due to the gender factor, Where the significance reached (0.007) in favor of females, with an average of (6,6200), whereas for males (53600) only in the physical dimension, while it was negative in the emotional, cognitive, and personal dimensions.4- There are no significant differences in psychological stress among computer and mobile phone users in terms of age, blood type, material status, and work sector, whether public or private.
Keywords: psychological stress; modern technologies; demographic variables; psychology